Proposal of Interaction Used Umbrella for Smartphone - Mori, Sohichiro; Oka, Makoto (Human Interface and the Management of Information: Information, Knowledge and Interaction Design, 2017)
In recent years, the hazards of operating on the smartphone while walking has become common knowledge today, and the behavior has become an object of public concern, frequently causing collisions between individuals and bicycles or cars. People operating on the smartphones while walking will inevitably gaze downward. Not being able to see what is in the front, they become involved in collisions. In this study, we will make it possible to operate smartphones using umbrellas. For this purpose, we will develop a system and interaction that will turn the umbrella into smartphones (allow the umbrella to perform the input and output operations of the smartphones). Our aim is to suggest and validate the interaction between the user and his/her umbrella. By using the umbrella as a display, users will be able to face forward while walking. We will validate through several apps whether it is possible to operate the smartphone using an umbrella.